Curcumin-loaded mixed micelles: preparation, optimization, physicochemical properties and cytotoxicity in vitro. (January 2015) - Duan, Yuwei; Wang, Juan; Yang, Xiaoye; Du, Hongliang; Xi, Yanwei; Zhai, Guangxi
Abstract Although curcumin (CUR) can inhibit proliferation and induce apoptosis of tumors, the poor water solubility restricted its clinical application. The aim of this study was to improve the aqueous solubility of CUR and make more favorable changes to bioactivity by preparing curcumin-loaded phospholipid-sodium deoxycholate-mixed micelles (CUR-PC-SDC-MMs). CUR-PC-SDC-MMs were prepared by the thin-film dispersion method. Based on the results of single factor exploration, the preparation technology was optimized using the central composite design-response surface methodology with drug loading and entrapment efficiency (EE%) as indicators. The images of transmission electron microscopy showed that the optimized CUR-PC-SDC-MMs were spherical and well dispersed. The average size of the mixed micelles was 66.5 nm, the zeta potential was about −26.96 mV and critical micelle concentration was 0.0087 g/l. CUR was encapsulated in PC-SDC-MMs with loading capacity of 13.12%, EE% of 87.58%, and the solubility of CUR in water was 3.14 mg/ml. The release results in vitro showed that the mixed micelles presented sustained release behavior compared to the propylene glycol solution of CUR. The IC50 values of CUR-loaded micelles and free drug in human breast carcinoma cell lines were 4.10 μg/ml and 6.93 µg/ml, respectively. It could be concluded from the above results that the CUR-PC-SDC-MMs system might serve as a promising nanocarrier to improve the solubility and bioactivity of CUR.